Traditional Handline Fishing in Pohuwato Regency, Indonesia - Lis M. Yapanto; Sitti Nursinar (Journal of International Conference Proceedings (JICP), 2020)
This study aims to determine the level of income of traditional handline fishing and its marketing efficiency in the Bumbulan Village, Paguat District, Pohuwato Regency, Gorontalo Province. This study used a survey method with questionnaires by interviews. The samples were selected by census of 33 fishermen. This study was conducted in December 2018 to October 2019. The results revealed the traditional handline fishermen average income is Rp. 4,073,030 per month. It is categorized as high income according to BPS (Central Bureau of Statistics).